Studying Hammer horror - Walden, Victoria Grace (Auteur, 2016)
Intended for students, fans, and general readers, this book transcends superficial preconceptions of Hammer horror in order to reach the essence of Hammer.
Keywords: Hammer Film Productions.; Hammer Film Productions; Horror films -- History and criticism.; Films d'horreur -- Histoire et critique.; Horror films; Criticism, interpretation, etc.